Tin isotope fractionation during experimental cassiterite smelting and its implication for tracing the tin sources of prehistoric metal artefacts - Berger, Daniel; Pernicka, Ernst (Journal of archaeological science, 2018)
Provenance studies of metal artefacts are well-established in the interdisciplinary field of science-based archaeology primarily using the chemical and isotopic composition. In the last decades, tin isotopes became gradually more important as a fingerprinting tool for the provenance of tin, but many questions especially regarding the behaviour of tin isotopes during pyrometallurgical processes are still not satisfactorily answered. This paper is a contribution to the understanding of tin isotope fractionation on tin ore smelting under prehistoric conditions and discusses the consequences for tin provenance studies. It presents the results of smelting experiments that were carried out with cassiterite in the laboratory and in the field, respectively. Besides chemical characterisation with XRF, SEM-EDX and Q-ICP-MS, tin isotope composition of tin ores and smelting products (tin metal, tin vapour, slag) were determined using solution MC-ICP-MS. Although tin recovery on smelting in the field was low (20–30%) due to tin losses to fuming and slag formation, the results indicate that the tin isotope composition is less affected than anticipated from theoretical considerations (Rayleigh fractionation). If cassiterite is completely reduced during the smelting reaction the tin metal becomes enriched in heavy tin isotopes with a fractionation of Δ124Sn=0.09–0.18‰ (0.02–0.05‰ u−1) relative to the original cassiterite. An estimate of the provenance of the original cassiterite and the potential ore source would still be possible because the variability of tin isotope ratios in tin ore provinces is much larger. If the cassiterite becomes incompletely reduced, however, then fractionation increases significantly up to Δ124Sn=0.88‰ (0.22‰ u−1) and conclusions on tin sources are limited. Similarly, condensed tin vapours (Δ124Sn=1.13‰ (0.28‰ u−1)) and slags (Δ124Sn=0.42–1.32‰ (0.11–0.33‰ u−1)) that are by-products of the smelting process show large fractionation with respect to the original tin ore as well, which makes them unsuitable for provenance studies.
Gesehen am 07.05.2019